2014
DOI: 10.1051/0004-6361/201424308
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of the Benešov bolide and recovery of polymict breccia meteorites – old mystery solved after 20 years

Abstract: The main motivation for this work was to explain and solve the old mystery connected with the detailed instrumental observation of the Benešov superbolide on 7 May 1991 over the central part of the Czech Republic. Detailed analyses of this undoubted meteorite fall were published in several papers, and this is one of the best documented bolides (at least of the superbolide category) ever observed. However, despite high-quality data, favorable trajectory, relatively large terminal mass, and especially great effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“…The initial disruption was severe -the largest fragments were of only 1 -2% of the original mass (∼ 25% in terms of size). But the low strength is in accordance with the heterogeneous nature of the recovered meteorites (Spurný et al 2014).…”
Section: J Borovičkasupporting
confidence: 57%
“…The initial disruption was severe -the largest fragments were of only 1 -2% of the original mass (∼ 25% in terms of size). But the low strength is in accordance with the heterogeneous nature of the recovered meteorites (Spurný et al 2014).…”
Section: J Borovičkasupporting
confidence: 57%
“…Žďár nad Sázavou is the fourth meteorite with precisely known orbit after Příbram in 1959 (Ceplecha ), Benešov in 1991 (Spurný et al. ), and Morávka in 2000 (Borovička et al. ) found in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…Zd' ar nad S azavou is the fourth meteorite with precisely known orbit after P r ıbram in 1959 (Ceplecha 1961), Bene sov in 1991 (Spurn y et al 2014), and Mor avka in 2000 found in the Czech Republic. All these exceptional cases were completely analyzed by the team from the Astronomical Institute of the CAS in Ond rejov.…”
Section: Discussionmentioning
confidence: 99%
“…However, their results were based on the assumption that, in order to preserve the impactor, an impact velocity 0.5 km/s is required, which is much smaller than the typical impact velocity (about 5 km/s) among random asteroids (Bottke et al 1994;O'Brien & Sykes 2011). The second confirmed case of heterogeneous meteorite is Benesov (Spurný et al 2014). Surprisingly, one meteorite was H chondrite, one was LL chondrite and one was LL chondrite with embedded achondritic clast.…”
Section: Introductionmentioning
confidence: 99%